2012
DOI: 10.1177/0748233712446723
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status in MgO nanoparticle-exposed rats

Abstract: In this present study, antioxidant status was evaluated in rat serum following exposure to magnesium oxide (MgO) nanoparticles. The lungs of rats were intratracheally instilled with (single dose) phosphate-buffered saline (PBS) + 1% of Tween 80 (solvent control) or MgO or carbonyl iron (negative control) or quartz particles (positive control) at a dose of 1 and 5 mg/kg of body weight. The blood samples were collected at 1, 7, and 30 days of postinstillation of nanoparticles after their exposure, and different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…A study reported on the antioxidant status in serum of rats after acute intratracheal instillation of MgO NPs. The results revealed oxidative stress due to the reduction in total antioxidant capacity . However, the consequences of repeated/chronic exposure to these NPs have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…A study reported on the antioxidant status in serum of rats after acute intratracheal instillation of MgO NPs. The results revealed oxidative stress due to the reduction in total antioxidant capacity . However, the consequences of repeated/chronic exposure to these NPs have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As one of the metal-based nanoparticles, MgO nanoparticles are widely used as catalyzer, redactor, humidity sensor, antibacterial agent and destructive sorbent for toxins, fluoride, and so on and in improving luminous efficiency for ultraviolet emission. 3,4 Recently, MgO-based magnetic tunnel junction sensor together with magnetic nanoparticles is being used as biosensors for liver cancer immunoassay, 5 and MgO nanoparticles have been informed as a promising material in nano-cryosurgery for tumor treatment. [4][5][6] Previous researches have shown that nanoparticles could be absorbed through the respiratory, digestive, or dermal route into the bloodstream and then could reach to secondary organs such as brain, heart, and liver.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recently, MgO-based magnetic tunnel junction sensor together with magnetic nanoparticles is being used as biosensors for liver cancer immunoassay, 5 and MgO nanoparticles have been informed as a promising material in nano-cryosurgery for tumor treatment. [4][5][6] Previous researches have shown that nanoparticles could be absorbed through the respiratory, digestive, or dermal route into the bloodstream and then could reach to secondary organs such as brain, heart, and liver. 7 Moreover, nanoparticles have been reported to frequently affect cellular molecules and have toxic effects such as oxidative damage, DNA damage, cell death, and morphological changes in the exposed organs or systems.…”
Section: Introductionmentioning
confidence: 99%
“…The wide applications of nanotechnology have increased the chance of human exposure to nanoparticles in their daily lives. Previous studies have demonstrated that nanoparticles can cause health effects systemically; both molecular and cellular levels were examined [ 23 25 ]. Silicon oxide nanoparticle families have been shown to be an important particle in industrial use but have also been shown to induce oxidative stress lipid peroxidation and cause damage to tissues and cells [ 10 15 , 26 ].…”
Section: Discussionmentioning
confidence: 99%